Gender differences in employers’ promotion preferences? : The role of working time, care obligations, and work–family policies - Wehner, Caroline [Verfasser]; Protsch, Paula [Verfasser]; De Grip, Andries [Verfasser] (My University, 2026)
"Despite considerable changes in recent decades, women and men still have different careers, fostering gender inequality in paid work. Women work more often part-time and have more care obligations, which are typically regarded as incongruent with leadership roles and might lead to career penalties. We investigate employers’ gender-related promotion preferences. Using a large factorial survey experiment across organizations in Germany enables us to disentangle employer preferences regarding gender from their promotion preferences on employees’ working time and care obligations. We find career penalties for working part-time as well as having care obligations, instead of gender as such. Work–family policies do not appear to equalize the promotion probability between employees having care obligations and those without any care obligations. These findings reflect the impact of gender inequality in the household on the career opportunities of women. They suggest that the lower promotion chances for women compared to men that are observed in practice are due to unequal distributions of care obligations and working part-time." (author's abstract; BIBB-Doku)
Der Artikel wurde zuerst am 05.05.2026 online first veröffentlicht.“
Keywords: G 2.4.5 Gender Mainstreaming; S 5.3 Personalentwicklung; G 1.3.3 Bildungs- & Erwerbsbiografien; 370; Personalpolitik; Bewerberauswahl; Geschlechtersegregation; Berufsverlauf; Chancengleichheit; Teilzeitarbeit; Beruf und Familie; Familienarbeit